The evolution of reptiles - Edwards, Sue Bradford (Animal evolution (Essential Library (Firm)), 2019)
Explores the evolution of reptiles from the earliest known prehistoric species through modern examples. Highlights important features in the evolution of various species, how the environment shaped these evolutionary features, and important discoveries made by scientists. Includes an additional facts section with a timeline, sidebars and color photographs, a glossary, source notes, and resources for further information.